Association of Interleukin-10 Methylation Levels With Gestational Diabetes in a Taiwanese Population - Kang, Jessica; Lee, Chien-Nan; Li, Hung-Yuan; Hsu, Kai-Han; Wang, Shu-Huei; Lin, Shin-Yu (Frontiers in Genetics, 2018)
Objective: Gestational diabetes mellitus (GDM) has been considered as is defined as glucose intolerance with onset during pregnancy, which is also an inflammatory disease and is associated with future metabolic diseases in both the patients and their offspring. The mechanisms remain largely unknown and are may be partly related to epigenetics. The aim of this study is to compare the methylation levels of the cytokine interleukin-10 (IL-10) in pregnant women and their fetuses under both hyperglycemic and euglycemic environment, whichthe results may be a clue to understanding the epigenetic pathway underlyingmechanisms underlying pathogenesis of GDM and future metabolic conditions. Methods: We analyzed the methylation levels of the IL-10 gene in maternal blood, cord blood and placental tissue in both GDM group (n=8) and non-GDMcontrol group (n=24) via LightCycler LC480 (Roche, Rotkreuz, Switzerland). IL-10 levels concentrations in maternal blood and THP-1 cells were measured by enzyme-linked immunosorbent assay (ELISA) using BD OptEIA Human IL-10 ELISA kit (BD Biosciences Pharmingen, California, USA). Results: The maternal blood IL-10 methylation levels in GDM group maternal blood before delivery werewas 0.23±0.04 and in the control group it was 0.26±0.04 (significantly lower in the GDM group (p=0.03), but there were no significant differences between groups in the cord blood (p=0.31) or or placental tissue (p=0.35). Increased IL-10 serum plasma concentrations were was discovered under in maternal blood of GDM hyperglycemia environmentgroup (p=0.002), and was were also confirmed viain the THP-1 cell line. Conclusions: Hypomethylation of maternal blood and increased serum plasma IL-10 concentrations in the maternal blood before birth were found in the GDM group.